Analisis Perbandingan Motivasi Kerja Antara Driver Ojek Online Gojek Dan Driver Ojek Online Grab Di Kota Medan Menurut Teori Kebutuhan Maslow - Rendy fachridan; Kustoro Budiarta (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2024)
The online motorcycle taxi profession has grown rapidly in Indonesia, becoming a job choice for many people due to its time flexibility and attractive earning opportunities. However, drivers face challenges related to revenue, well-being, and relationships with platform companies. With the Maslow Needs Theory approach, this study aims to analyze the comparison of work motivation between Gojek and Grab online motorcycle taxi drivers in Medan City using the Maslow Needs Theory approach. Data was collected in October 2024 through a quantitative method with a questionnaire distributed to 100 drivers from each platform using accidental sampling techniques. This study measures the five basic needs in Maslow's Theory, namely physiological, security, social, rewarding, and self-actualization needs. Data analysis uses the Independent T-Test with the help of SPSS The results showed that there were no significant differences in physiological, safety, social, rewarding, and self-actualization needs between the two driver groups. These results show that the fulfillment of needs in the five levels of Maslow's Needs Theory plays an important role in influencing the work motivation of online motorcycle taxi drivers. The implication of these findings is that online motorcycle taxi service providers, such as Gojek and Grab, can improve driver motivation and performance with policies that support the fulfillment of driver needs according to Maslow's theory of needs.